2011
DOI: 10.1007/s12306-011-0125-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term result after traumatic anterior shoulder dislocation: what works best?

Abstract: Traumatic anterior shoulder dislocation is a common pathology. To inform the patient, it is therefore important to know the natural history of anterior dislocation and the long-term result of conservative treatment versus the long-term results of operative treatment. In this review article, we compare the effectiveness of various anatomical and non-anatomical interventions and between open and arthroscopic surgery. Evaluating of the result, we focused on the recurrence of instability, return to sport, and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The operative management of traumatic anterior glenohumeral instability has evolved from open to arthroscopic stabilization techniques. However, controversy over the results of open or arthroscopic shoulder stabilization still exists [1][2][3][4] . Advocates of arthroscopy cite faster recovery, less postoperative pain, decreased operative time, improved cosmetic appearance, improved range of shoulder motion, and more accurate identification of intra-articular pathology 1,5,6 .…”
mentioning
confidence: 99%
“…The operative management of traumatic anterior glenohumeral instability has evolved from open to arthroscopic stabilization techniques. However, controversy over the results of open or arthroscopic shoulder stabilization still exists [1][2][3][4] . Advocates of arthroscopy cite faster recovery, less postoperative pain, decreased operative time, improved cosmetic appearance, improved range of shoulder motion, and more accurate identification of intra-articular pathology 1,5,6 .…”
mentioning
confidence: 99%
“…The most recently published studies by Finestone et al [6] and Liavaag et al [7] deemed the operative treatment to be the more efficient treatment for primary traumatic dislocation, even though a direct comparison between immobilization in external rotation and surgery is not available as a randomized controlled trial. In contrast to immobilization in internal rotation, recurrence rates of operative treatment are clearly superior [24,[26][27][28]. Although the risks for surgery, especially in arthroscopic stabilization, are low [28][29][30], these risks have to be considered and disclosed to the patient during the decision-making process.…”
Section: Studymentioning
confidence: 99%
“…In contrast to immobilization in internal rotation, recurrence rates of operative treatment are clearly superior [24,[26][27][28]. Although the risks for surgery, especially in arthroscopic stabilization, are low [28][29][30], these risks have to be considered and disclosed to the patient during the decision-making process. Moreover, the 19 % with instability after 5 years should be critically discussed despite the good results of the remaining patients.…”
Section: Studymentioning
confidence: 99%
“…[6] have suggested that labral, ligamentous and osseous pathology in shoulder instability are time- and recurrence dependent. Therefore, it appears to be the sub-group of young athletic males engaged in demanding activities that may profit more from rather early operative management of shoulder instability [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Avoiding numerous pre-operative dislocations appears to prevent to some extent the occurrence and severity of post-operative dislocation arthropathy [19]. One should point out however that the clinical significance of radiologically evident dislocation arthropathy is debatable, as Constant score results do not seem to correlate with the presence or grade of postoperative dislocation arthropathy [8, 19]. …”
Section: Introductionmentioning
confidence: 99%